Catalyst-Free Microwave Digestion and Estimation of Nitrogen and Phosphorus Contents in Chicken Manure Adopting Competitive Analytical Methods. Issue 15 (22nd August 2021) - Niaz, Basit; Zahid, Faisal Maqbool; Hongjuan, Li; Wei, Wang; Lizhi, Yu; Niaz, Yasir; Iftikhar, Fatima; Dong, Renjie
ABSTRACT: For enhanced soil fertility, the application of animal manure has been recognized as an alternative mean to synthetic fertilizers. A major issue in current manure application practices is the rapid, reliable estimation of nutrients, such as nitrogen (N) and phosphorus (P). Estimation of N and P in manure involves the use of harsh chemicals and conditions, and considerable analytical time. In this work, microwave-assisted digestion condition is being reported for N and P estimation into chicken fermentation slurry. At comparative lower temperature 200°C and duration 1 h, digestion involves the use of half of the amount of acid and that too without the aid of a catalyst. Furthermore, N and P contents were determined from automatic Kjeldahl (AKj), manual Kjeldahl (MKj) and flow injection methods (FIA). The advantage of FIA is that it provides simultaneous detection of P and N. Additionally; P contents were analyzed and compared by colorimeter (Clr). To obtain a clear view of the performance of competing analytical procedures, a single sample analysis (SSA) time was measured. Thus, for N estimation; the SSA by AKj was superior, i.e., , AKj ˃ MKj ˃ FIA which was 6:10:70 mins, respectively, and for P; Clr˃FIA which was 30:70 mins, respectively. However, when the adoptive methods were judged on the basis of effectiveness or by overall performance/ease in handling, the order of competing methods for N became AKj ˃ FIA ˃ MKj and for P it was FIA ˃ Clr. Statistical evaluations from the analytical data were also in accordance.